Contextualizing the Decalogue The Invention of the Ten-Commandments in Late Ancient Christianity - Bick, Shraga (2025)
This article argues that while several Decalogue precepts are mentioned in the New Testament, the Decalogue as a distinct normative category is completely absent. This goes in line with the evidence from Second Temple Jewish sources, where very limited attention is given to the Decalogue, with Philo serving as an exception. I further propose that the formation of the Decalogue as a distinct normative category comes accompanied by a specific anti-Jewish discourse, beginning in the late second century and continuing into the fourth century. Authors such as Irenaeus of Lyon, Ptolemy, Aphrahat, and the anonymous author of the Syriac Book of Steps construct ‘the Decalogue’ as a category for commandments that Christians must still follow, as opposed to the rest of Law. The latter is characterized as ‘not good laws’, given to the Jews only on account of their sins.
Keywords: Ptolemy; Polemics; New Testament; Law; Judaism; Irenaeus; Decalogue